Ответ:
Пошаговое объяснение:
1)2 3/5:(х+1 3/14)-1 2/5=1/3
2 3/5 : (x + 1 3/14) = 1/3 + 1 2/5
2 3/5 : (x + 1 3/14) = 5/15 + 1 6/15
2 3/5 : (x + 1 3/14) = 1 11/15
x + 1 3/14 = 2 3/5 : 1 11/15
x + 1 3/14 = 13/5 * 15/26
x + 1 3/14 = 3/2
x = 3/2 - 1 3/14
x = 21/14 - 17/14
x = 4/14
x = 2/7
2)(х-3/8)*8/35+2 2/7=2 3/5
(x - 3/8 )*8/35 = 2 3/5 - 2 2/7
(x - 3/8 )*8/35 = 2 21/35 - 2 10/35
(x - 3/8 )*8/35 = 11/35
x - 3/8 = 11/35 * 35/8
x - 3/8 = 11/8
x = 11/8 + 3/8
x = 14/8 = 7/4
x = 1 3/4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1)2 3/5:(х+1 3/14)-1 2/5=1/3
2 3/5 : (x + 1 3/14) = 1/3 + 1 2/5
2 3/5 : (x + 1 3/14) = 5/15 + 1 6/15
2 3/5 : (x + 1 3/14) = 1 11/15
x + 1 3/14 = 2 3/5 : 1 11/15
x + 1 3/14 = 13/5 * 15/26
x + 1 3/14 = 3/2
x = 3/2 - 1 3/14
x = 21/14 - 17/14
x = 4/14
x = 2/7
2)(х-3/8)*8/35+2 2/7=2 3/5
(x - 3/8 )*8/35 = 2 3/5 - 2 2/7
(x - 3/8 )*8/35 = 2 21/35 - 2 10/35
(x - 3/8 )*8/35 = 11/35
x - 3/8 = 11/35 * 35/8
x - 3/8 = 11/8
x = 11/8 + 3/8
x = 14/8 = 7/4
x = 1 3/4